PENGARUH VARIASI JUMLAH POMPA TERHADAP PERFORMA MESIN SPRAYER DORONG - Xander Salahudin; Sri Widodo; Aris Priyatmoko; Miftahkul Khoir (Journal of Mechanical Engineering, 2018)
Knapsack sprayer is the most widely used type of sprayer by farmers, but it is quite tiring when used, because it has to carry a sprayer weighing up to 15 kg and manually pumping to get the pressure requirement in the tank (pressure required of 2 - 7 kg / cm2). Based on these problems, researchers innovate with a new type of sprayer (utilizing wheel rotation that is converted into translational motion to press the pump). The purpose of this study is analyze the influence of the number of pumps to resulting pressure. The study was conducted with 5 repetitions and the distance of experiment was 25 meter. The results show that the number of pumps has little effect, since the number of pumps has no direct effect on the amount of compressed air (this is affected by the same total pumping distance between the use of 1 pump and 2 pumps). Testing using 1 pump and 2 pumps produced a pressure between 1.9 - 2.2 kg / cm2.Keywords: knapsack, sprayer, creative technology.